A disinhibitory nigra-parafascicular pathway amplifies seizure in temporal lobe epilepsy - Bin Chen (Nature Portfolio, 2020)
The neural circuits through which the substantia nigra pars reticulata (SNr) exerts its role in epilepsy control are not known. Here the authors reveal that a long-range SNr-parafascicular nucleus disinhibitory circuit participates in regulating seizures in temporal lobe epilepsy and inhibition of this circuit can alleviate severity of epileptic seizures.